EFFECTS OF CLIMATE CHANGE ON THE SUSTAINABLE DEVELOPMENT OF RESIDENTIAL AREAS AT HO CHI MINH CITY - Việt (Journal of Military Science and Technology, 2020)
The main objectives of sustainable development are improving the environmental, social and economic quality. This study aims to assess the sustainable development based on three factors including economy – society – environment at Ho Chi Minh City with the case study in southern area. The results showed that this area list in low sustaibale level with the Population sustainable development index (PoSDI) ranging between 0.280-0.305. In conclusion, this problem lead to the negative consequences such as increasing migration and poverty which could disrupt household structure.